Type I interferon response and vascular alteration in chilblain‐like lesions during the COVID‐19 outbreak. (1st December 2021) - Frumholtz, L.; Bouaziz, J.‐D.; Battistella, M.; Hadjadj, J.; Chocron, R.; Bengoufa, D.; Le Buanec, H.; Barnabei, L.; Meynier, S.; Schwartz, O.; Grzelak, L.; Smith, N.; et al.
Summary: Background: The outbreak of chilblain‐like lesions (CLL) during the COVID‐19 pandemic has been reported extensively, potentially related to SARS‐CoV‐2 infection, yet its underlying pathophysiology is unclear. Objectives: To study skin and blood endothelial and immune system activation in CLL in comparison with healthy controls and seasonal chilblains (SC), defined as cold‐induced sporadic chilblains occurring during 2015 and 2019 with exclusion of chilblain lupus. Methods: This observational study was conducted during 9–16 April 2020 at Saint‐Louis Hospital, Paris, France. All patients referred with CLL seen during this period of the COVID‐19 pandemic were included in this study. We excluded patients with a history of chilblains or chilblain lupus. Fifty patients were included. Results: Histological patterns were similar and transcriptomic signatures overlapped in both the CLL and SC groups, with type I interferon polarization and a cytotoxic–natural killer gene signature. CLL were characterized by higher IgA tissue deposition and more significant transcriptomic activation of complement and angiogenesis factors compared with SC. We observed in CLL a systemic immune response associated with IgA antineutrophil cytoplasmic antibodies in 73% of patients, and elevated type I interferon blood signature in comparison with healthy controls. Finally, using blood biomarkers related to endothelial dysfunction and activation, and to angiogenesis or endothelial progenitor cell mobilization, we confirmed endothelial dysfunction in CLL. Conclusions: Our findings support an activation loop in the skin in CLL associated with endothelial alteration and immune infiltration of cytotoxic and type I IFN‐polarized cells leading to clinical manifestations.